2022
DOI: 10.3389/fpsyg.2022.811712
|View full text |Cite
|
Sign up to set email alerts
|

What Individuals Experience During Visuo-Spatial Working Memory Task Performance: An Exploratory Phenomenological Study

Abstract: In experimental cognitive psychology, objects of inquiry are typically operationalized with psychological tasks. When interpreting results from such tasks, we focus primarily on behavioral measures such as reaction times and accuracy rather than experiences – i.e., phenomenology – associated with the task, and posit that the tasks elicit the desired cognitive phenomenon. Evaluating whether the tasks indeed elicit the desired phenomenon can be facilitated by understanding the experience during task performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…The study of individual experience during a psychological task using a phenomenological approach is a relatively new area of research (Berkovich‐Ohana et al., 2020). In our recent work (Oblak et al., 2022), using a combination of change detection tasks and in‐depth phenomenological interviews, we identified a set of 18 cognitive strategies that participants used to perform the task. We categorized the identified strategies into active and passive strategies based on perceived engagement and into encoding, maintenance, and retrieval strategies based on the phase of the task to which they related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of individual experience during a psychological task using a phenomenological approach is a relatively new area of research (Berkovich‐Ohana et al., 2020). In our recent work (Oblak et al., 2022), using a combination of change detection tasks and in‐depth phenomenological interviews, we identified a set of 18 cognitive strategies that participants used to perform the task. We categorized the identified strategies into active and passive strategies based on perceived engagement and into encoding, maintenance, and retrieval strategies based on the phase of the task to which they related.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, in our recent study (Oblak, Slana Ozimič, Repovš, & Kordeš, 2022), we took the first steps toward examining the full range of phenomenology of working memory task performance. Participants were instructed to remember colors, orientations, or positions of stimuli presented in a change detection task.…”
Section: Introductionmentioning
confidence: 99%
“…Although strategies have also been studied using openended questions, e.g., by simply asking participants about the memory strategies they used in a task (e.g., Miller et al, 2012), to our knowledge, an in-depth phenomenological study (Berkovich-Ohana et al, 2020; Hurlburt, 2011; Petitmengin, 2006) of individuals' experiences related to performing a working memory task, including strategies, has never been conducted. In our recent study (Oblak et al, 2022), we took the first steps toward examining the full range of phenomenology of working memory task performance. Participants were instructed to remember colors, orientations, or positions of stimuli presented in a change detection task.…”
Section: Introductionmentioning
confidence: 99%
“…This division of experiences has previously 139 been described in consciousness research (Colombetti, The phenomena at the front of consciousness are rela-151 tively effable, that is, there are concepts and terms that can 152 be readily applied to them (Jaspers, 1997). Analysis of the 153 phenomena at the front of consciousness (Oblak et al, 2022) 154 revealed that they included experiential categories that were 155 directly related to the performance of the working memory 156 task and could be defined with reference to the structure of Participants who were unable to provide valid experiential reports 1 (N = 7) and who did not participate in all three between them (codebook available at https://osf.io/mkp8b/; Oblak et al, 2022). For the purpose of this paper, we have slightly adjusted the names of some of the L2 categories, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation